Rommel's Desert Army - Windrow, Martin; Color Plates by Roffe, Michael (London Osprey Publications, 1976)
The desert war produced commanders of dash and originality on both sides and the memory of the German commanding general, Erwin Rommel, has endured as the epitome of skill, daring and soldierly integrity. His victories in World War II were brilliant until he was bested by poor health, lack of reinforcements and an opposing commander who was his equal. The contribution of his various troops is detailed in a full order of battle which includes his veteran Afrika Korps and Italian allies, and their uniforms are shown in full color artwork.
Include Illustrations.
Keywords: Germany. Heer. Panzerarmeekorps Afrika -- Military campaigns -- World War (1939-1945) -- Uniforms -- Germany -- Africa -- Germany. Heer -- Regimental histories